Immunomodulatory and Growth Promoting Effect of Dietary Fenugreek Seeds in Fingerlings of Common Carp (Cyprinus carpio Lin.) - Kumar, Amresh; Vasmatkar, Pashupat; Baral, Pratibha; Agarawal, Sanjeev; Mishra, Ashutosh (Fishery Technology, 2017)
The aim of the study was to determine the immunomodulatory effect of dietary intake of fenugreek (Trigonella foenumgraecum L.), seed powder on common carp (Cyprinus carpio Lin.). The diets containing 5, 10 and 20 g fenugreek kg-1 of dry feed at the rate of 5% of total body weight was fed to fish for 90 days. Experimental fish stock was challenged intra-peritoneally with Aeromonas hydrophila. Total erythrocyte count, haemoglobin count, total serum protein, albumin and globulin content were determined. Results indicate that the values of these parameters were significantly enhanced in fenugreek supplemented groups particularly in 20 mg kg-1of body weight. Highest lysozyme and nitrobluetetrazolium activity were 65.16 Â± 0.585 and 0.989 Â± 0.004 respectively in 10 g kg-1 post challenge group. The survival percentage and specific growth rate was higher (98.34%) in 20 mg kg-1 group with respect to control. Furthermore, the antibacterial activity of fenugreek methanolic extract was also observed against two fish pathogens; Aeromonas hydrophila and Pseudomonas liquefaciens. The findings clearly indicate that the incorporation of fenugreek in diet of common carp fingerlings enhances the non-specific immunity which increases their resistance against infection in fish, suggesting its use in fish diet as a health supplement.